Efficient Resource Allocation Using Optimized Data Stack Technique in Cloud - N. Sureshbabu (International Journal of Intelligent Systems and Applications in Engineering, 2024)
A wide range of advantageous features, including resource pooling, rapid elasticity, approximated services, on-demand self-services, and more, have made cloud computing extremely popular. But distributing resources securely among users with better authentication and privacy is a difficult problem in cloud networks. Thus, for the equitable exploitation of storage resources, an effective cloud resource design is suggested in this work. The information is kept up to date, organized, and available to authorized users with enhanced allocation properties that remove internal dangers. By supplying a unique storage key, the Optimized Data Stack (ODS) encryption technique locates the right storage site and efficiently allocates resources. The suggested method gives users immediate access to storage sites while offering high privacy and enhanced secrecy. Using Visual C#, the simulation is run, and the results show that the suggested method allocates resources quickly while making effective use of cloud server storage.